Building Social Media Engagement on Instagram by Using Visual Aesthetics and Message Orientation Strategy: A Content Analysis on Instagram Content of Indonesia Tourism Destinations - Sony Kusumasondjaja (AIBPM Publisher, 2021)
The purpose of this study is to investigate the differences in consumer engagement to Instagram content of tourist destinations when the content uses different types of visual aesthetics and message orientation. A content analysis of 1158 Instagram content posted by official accounts of Indonesia priority tourist destinations was conducted. This study finds that when content with classical aesthetics gained stronger consumer engagement than the one with expressive aesthetics, however content using different types of message orientation does not result in different level of consumer engagement. Interaction effects suggest that content using a combination of classical aesthetics and interaction orientation gets better consumer engagement than any other combinations of aesthetics and orientation. Meanwhile, content using expressive aesthetics and self-orientation gains the least consumer engagement than any other combinations of aesthetics and orientation. These findings indicate that visual elements of an Instagram content tend to be more powerful to elicit consumer responses than verbal elements of the content. This is expected to offer important contributions to destination marketers and social media administrators to pay more attention to visual elements than to verbal aspects of the content when designing social media information.